2019
DOI: 10.1080/2162402x.2019.1614857
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous BCG enhances innate effector antitumor cytotoxicity during treatment of bladder cancer: a translational clinical trial

Abstract: Background: Intravesical bacillus Calmette-Guérin (BCG) is the gold standard immunologic agent for treating patients with high-grade non-muscle invasive bladder cancer (NMIBC). Nevertheless, relapse rates remain high and BCG unresponsive NMIBC often requires bladder removal. Preclinical data suggest that priming with percutaneous BCG vaccine could improve response to intravesical BCG. Methods: A single-arm trial (NCT02326168) was performed to study the safety, immunogenicity, and preliminary efficacy of primin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…17 γδ T cells are required for effective BCG treatment of mouse bladder cancer 16 and BCG enhances cytotoxicity of γδ T cells against human bladder cancer. 18 Our group and others have shown that rapamycin increases the proliferative capacity and effector function of γδ T cells. [19][20][21] Moreover, rapamycin boosts human γδ T cellmediated killing of human squamous cell carcinoma in a mouse xenograft model.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…17 γδ T cells are required for effective BCG treatment of mouse bladder cancer 16 and BCG enhances cytotoxicity of γδ T cells against human bladder cancer. 18 Our group and others have shown that rapamycin increases the proliferative capacity and effector function of γδ T cells. [19][20][21] Moreover, rapamycin boosts human γδ T cellmediated killing of human squamous cell carcinoma in a mouse xenograft model.…”
Section: Introductionmentioning
confidence: 95%
“…Human urinary cytokine-luminex assay Urine samples were diluted 1:20 with high-performance liquid chromatography grade water and measured for urinary creatinine level according to the manufacturer's instructions using the Creatinine Colorimetric Assay Kit (Cayman Chemical) and a Synergy 2 plate reader (BioTek). 18 Undiluted or diluted (1:1) samples were also run in duplicates using a Milliplex MAP 6-plex human cytokine panel (Millipore), and analyzed using FLEXMAP 3D and xPONENT software (Luminex). Average cytokine concentration of each urine sample was normalized based on its creatinine level to correct for bladder urine volume (at 100 mg/dL creatinine).…”
Section: Bcg Stock Preparationmentioning
confidence: 99%
“…41,49 It is worth noting that Ji et al (2019) recently demonstrated the safety of BCG priming in NMIBC patients as well as the different responses of enhanced innate effector cells against some specific BC cell lines, suggesting a potential BCG resistance mechanism that could explain BCG nonresponsivity in some individuals. 50 On the other hand, optimum maintenance schedule has not been clarified. 51 Differences among the studies in the tumor stage of patients, treatment schedules, dose, BCG substrain and other parameters complicate the aim of achieving the best BCG maintenance schedule, and consequently, further research is needed to maximize the effect of the current treatment.…”
Section: Modification Of Schedules Priming-boosting Strategymentioning
confidence: 99%
“…The Phase II study NCT03519256, enrolling subjects with high-risk, non-MIBC, is monitoring the therapeutic profile of BMS-986205 combined with two drugs already approved for some types of bladder cancer such as nivolumab [200][201][202][203][204] and the toll like receptor 2 (TLR2)/TLR4 agonist [205][206][207][208][209] bacillus Calmette-Guérin (BCG). [210][211][212] Along similar lines, the Phase III study NCT03661320 compared the efficacy, tolerability and safety of three therapeutic regimens for MIBC: neoadjuvant standard of care chemotherapy with cisplatin [213][214][215][216][217] and gemcitabine, 218,219 (NAC) versus NAC combined with nivolumab or nivolumab plus BMS-986205, followed by continuation of adjuvant immunotherapy (nivolumab with or without the IDO1 inhibitor) post radical cystectomy. 220 Additionally, four ongoing studies aim at elucidating the therapeutic profile of BMS-986205 in combination with nivolumab in patients affected by endometrial carcinoma or endometrial carcinosarcoma (NCT04106414), unresectable or metastatic HCC (NCT03695250), stage II to IV HNSCC (NCT03854032), as well as stage III or IV melanoma (NCT04007588).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…The Phase II study NCT03519256, enrolling subjects with high-risk, non-MIBC, is monitoring the therapeutic profile of BMS-986205 combined with two drugs already approved for some types of bladder cancer such as nivolumab 200 - 204 and the toll like receptor 2 (TLR2)/TLR4 agonist 205 - 209 bacillus Calmette–Guérin (BCG). 210 212 Along similar lines, the Phase III study NCT03661320 compared the efficacy, tolerability and safety of three therapeutic regimens for MIBC: neoadjuvant standard of care chemotherapy with cisplatin 213 - 217 and gemcitabine, 218 , 219 (NAC) versus NAC combined with nivolumab or nivolumab plus BMS-986205, followed by continuation of adjuvant immunotherapy (nivolumab with or without the IDO1 inhibitor) post radical cystectomy. 220 …”
Section: Translational and Clinical Progressmentioning
confidence: 99%